Synthesis And Characterization Of Zinc Oxide Nanoparticles Using Ascorbic Acid For Evaluation Of Antioxidant Activity - Zakree, Syed Muhammad Al Hafiz Syed (Universiti Sains Malaysia, 2022)
Synthesis of metal oxide nanoparticles using ascorbic acid has become one of the focus of researchers over the past decades due to its lower energy consumption and cheaper alternative. In this research, zinc oxide nanoparticles (ZnO NPs) were synthesized by a chemical precipitation method. A precursor zinc acetate dihydrate and ascorbic acid act as reducing agent were used. The effects of solution pH and the concentration ratios of ascorbic acid to zinc acetate dihydrate (AA:Zn) were the chosen parameters to be studies. Over the range of pH studied at a constant AA:Zn of 1.0, pH 11 was found the best based on the highest absorption peak at 355 nm and the highest absorbance of 0.92 that was measured using the Ultraviolet Visible spectrometer (UV-Vis). It was found that the presence of ZnO was displayed from the Fourier-Transform Infrared Spectroscopy (FTIR) spectra at the wavenumber range of 470-520 cm-1 for all samples. SEM analysis showed that the nucleation and size of particles were decreased as the solution pH increased. The concentration ratios of ascorbic acid to zinc acetate dihydrate (AA:Zn) were changed from 1.0 to 4.0 while keeping the optimum pH of 11. Particle sizes, purity and morphology were study using Ultraviolet Visible spectrometer (UV-Vis), Energy Dispersed X-ray (EDX), and Scanning Electron Microscope (SEM). SEM analysis showed that the size and aggregation of particles decreased as the concentration increased. EDX analysis verified that the synthesized ZnO NPs has a higher purity because of the high composition of Zn and O. UV-vis spectra results showed the absorption band at 355 nm, 365 nm, 359 nm, 355 nm and 350 nm for ncentration ratio of AA:Zn 1.0, 1.5, 3.0, 3.5 and 4.0, respectively. Antioxidant activity of the synthesized ZnO NPs was determined by using 2,2-diphenyl-1-picrylhydrazyl (DPPH) and 2,2-azino-bis-(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) radical scavenging assay. The IC50 values of the synthesized ZnO NPs were 29.38 and 27.65 μg/ml for both DPPH and ABTS, respectively, which were lower than the standard ascorbic acid. The current research suggests that the synthesized ZnO NPs can be a substitute to the chemical drugs against antibiotic resistant foodborne pathogens.